Chiari Malformation and Attention Deficit Hyperactivity Disorder - Anaïs DuBow; Aurélie Mourot; Smadar Valérie Tourjman (Case Reports in Medicine)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition characterized by inattention, hyperactivity, and impulsivity. Chiari malformations (CM), first described approximately a hundred years ago, refer to a spectrum of hindbrain malformations characterized by cerebellar herniation through the foramen magnum. We present the case of a 28-year-old woman with ADHD and concurrent Chiari malformation type I (CM-I) that was diagnosed by CT scan. There is growing evidence supporting the role of the cerebellum and its associated structures in the pathophysiology of ADHD. Thus, a cerebellar malformation such as CM may impact neurological circuitry in a manner favoring the development of a neuropsychiatric disorder such as ADHD. Our case highlights the need for further studies pertaining to the role of the cerebellum in the pathophysiology of ADHD and the importance of considering the presence of CM when evaluating a patient with ADHD.